Death certificates utility in the death cause determination by ovarian cancer in Colombia in 2008 (2014)
Objective: To identify the direct causes and demographic characteristics of deaths from ovarian cancer in Colombia according to data provided by death certificates. Materials and methods: Direct causes of death in women whose underlying cause of decease was ovarian malignancy as recorded by the National Department of Statistics of Colombia in 2008 were reviewed. Distribution was evaluated by the direct cause of death, age, educational level, marital status, social security and site of death. These last variables are also analyzed by age groups. Results: There were 686 deaths, aged between 13 years and 104 years, with an average age of 61,6 years [95% CI: 35.01 to 85.1]. The main direct causes of death were respiratory insufficiency or failure in 128 (18.6%), multiple organ failure in 99 (14.4%), ovarian cancer in 94 (13.7%), cardiopulmonary arrest in 82 (11.9%), septic shock or sepsis 34 (4.9%) and in 29 gross metastatic disease (4.2%). Conclusions: The main direct causes of death recorded on death certificates are non-specific or they are associated with other diseases or the underlying cause is assumed to be the direct cause of death showing errors in the correct filling out of this document in Colombia.